1989
DOI: 10.1111/j.1432-1033.1989.tb14848.x
|View full text |Cite
|
Sign up to set email alerts
|

Insect immunity. Isolation of cDNA clones corresponding to diptericin, an inducible antibacterial peptide from Phormia terranovae (Diptera)

Abstract: We have previously isolated and characterized a family of novel 8-kDa cationic antibacterial peptides synthesized by larvae of Phorrnia terranovae (Diptera) in response to various injuries. These molecules have been named diptericins. The peptide sequence of diptericin A was used to prepare oligonucleotides for screening cDNA libraries and we report in the present paper the isolation of several cDNA clones encoding diptericin. The analysis of the nucleotide sequences indicates that diptericin is synthesized as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Both tenecin-4 and hemiptericin share ~22% identity to H. gloveri gloverin, but tenecin-4 has higher identity (22–24%) to H. virescens and T. ni gloverins than hemiptericin (15–17% identity). Other glycine-rich peptides are 7–10 kDa, such as P. terranovae and D. melanogaster diptericins (82 residues) (Dimarcq et al, 1988; Reichhart et al, 1989; Wicker et al, 1990), S. peregrina sarcotoxin-III (7 kDa) (Baba et al, 1987), Zophobas atratus and Allomyrina dichotoma coleoptericins (72–74 residues) (Bulet et al, 1991; Sagisaka et al, 2001), H. diomphalia holotricin-2 (72 residues) (Lee et al, 1994), Acalolepta luxuriosa acaloleptins (~8 kDa) (Imamura et al, 1999), and honeybee hymenoptaecin (93 residues) (Casteels et al, 1993). These glycine-rich peptides have activities against Gram-negative and Gram-positive bacteria.…”
Section: Gloverinsmentioning
confidence: 99%
“…Both tenecin-4 and hemiptericin share ~22% identity to H. gloveri gloverin, but tenecin-4 has higher identity (22–24%) to H. virescens and T. ni gloverins than hemiptericin (15–17% identity). Other glycine-rich peptides are 7–10 kDa, such as P. terranovae and D. melanogaster diptericins (82 residues) (Dimarcq et al, 1988; Reichhart et al, 1989; Wicker et al, 1990), S. peregrina sarcotoxin-III (7 kDa) (Baba et al, 1987), Zophobas atratus and Allomyrina dichotoma coleoptericins (72–74 residues) (Bulet et al, 1991; Sagisaka et al, 2001), H. diomphalia holotricin-2 (72 residues) (Lee et al, 1994), Acalolepta luxuriosa acaloleptins (~8 kDa) (Imamura et al, 1999), and honeybee hymenoptaecin (93 residues) (Casteels et al, 1993). These glycine-rich peptides have activities against Gram-negative and Gram-positive bacteria.…”
Section: Gloverinsmentioning
confidence: 99%
“…We used an oligonucleotide probe corresponding to the peptide sequence of the newly-isolated diptericin from the fleshfly Phormia terranovae [22]. A fourth cecropin gene (C), encoding a peptide which differs from cecropin A by three conservative amino-acid replacements, was later described [23].…”
Section: The Inducible Antibacterial Pep-tides Of Drosophilamentioning
confidence: 99%
“…Furthermore, the measured mass compared to the predicted mass (4060.6 Da) from the amino acid sequence, eliminated any possibility of post-translational modifications involving variations of more than 1 Da. A monoisotopic mass measurement (measured, 4057.90 Da; expected, 4057.81 Da) with an accuracy better than 0.1 Da was also achieved [l] and it was thus possible to demonstrate that the C-terminus was not amidated (expected mass difference of -1 Da) although this has been described for other antibacterial peptides like cecropin isolated from Hyalophora cecropia [2] and the related sarcotoxin IA isolated from Sarcophaga peregrina [3], as well as diptericin isolated from P. terranovae [4]. Finally, the data obtained from mass spectrometry measurements also showed that natural insect defensin A was not present in a covalent dimeric form since the molecular ion did not exhibit peaks separated by mjz 0.5, and no peak was detected at mjz 8120 [l].…”
Section: ---mentioning
confidence: 92%
“…The LSIMS spectrum for both peptides presents the protonated molecular ion at mjz 889. 4 and two peaks at m/z 401.2 and 491.2, corresponding to the protonated molec-- Table 1. Measured m/z of the major peaks from Fig.…”
Section: Purification and Identification Of The Disulfiae-containing mentioning
confidence: 99%